Genetic variation in open pollinated provenances/progenies tests of Eucalyptus dunnii Maiden - Schenone, Raúl Alberto; Storck, Lindolfo; Pimentel Martins-Corder, Maisa (Bosque (Valdivia), 2002)
Two opened-up-pollination tests were conducted at Ipatinga and Guanhães in the state of Minas Gerais to study the growth, adaptability and genetic variability of offspring of Eucalyptus dunnii. The tests were set up in a statistical delineation of compact-block families where the main plots corresponded to the provenances and the secondary plots corresponded to the offspring inside the provenances. Six trees row plot were used with ten repetitions. Height, diameter to breast height, cylindrical volume and plant survival were evaluated at Ipatinga and Guanhães at 42 and 40 months, respectively. The results showed that the growth in diameter height and volume was high in both towns, while highly significant differences were detected at the provenance level for plant survival at Guanhães. Mortality was high at Ipatinga. For diameter, height and cylindrical volume of plants, highly significant differences were detected at the family level. Heritability values at Guanhães were high.